Diversity and genomic insights into the uncultured Chloroflexi from the human microbiota. (17th April 2014) - Campbell, Alisha G.; Schwientek, Patrick; Vishnivetskaya, Tatiana; Woyke, Tanja; Levy, Shawn; Beall, Clifford J.; Griffen, Ann; Leys, Eugene; Podar, Mircea
Summary Many microbial phyla that are widely distributed in open environments have few or no representatives within animal‐associated microbiota. Among them, the Chloroflexi comprises taxonomically and physiologically diverse lineages adapted to a wide range of aquatic and terrestrial habitats. A distinct group of uncultured chloroflexi related to free‐living anaerobic Anaerolineae inhabits the mammalian gastrointestinal tract and includes low‐abundance human oral bacteria that appear to proliferate in periodontitis. Using a single‐cell genomics approach, we obtained the first draft genomic reconstruction for these organisms and compared their inferred metabolic potential with free‐living chloroflexi. Genomic data suggest that oral chloroflexi are anaerobic heterotrophs, encoding abundant carbohydrate transport and metabolism functionalities, similar to those seen in environmental Anaerolineae isolates. The presence of genes for a unique phosphotransferase system and N‐acetylglucosamine metabolism suggests an important ecological niche for oral chloroflexi in scavenging material from lysed bacterial cells and the human tissue. The inferred ability to produce sialic acid for cell membrane decoration may enable them to evade the host defence system and colonize the subgingival space. As with other low abundance but persistent members of the microbiota, discerning community and host factors that influence the proliferation of oral chloroflexi may help understand the emergence of oral pathogens and the microbiota dynamics in health and disease states.